1999
DOI: 10.1038/sj.ejcn.1600833
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of dietary triacylglycerols from olive oil and high-oleic sunflower oil into VLDL triacylglycerols of hypertensive patients

Abstract: Objectives: To establish whether the ingestion of diets enriched with olive oil or high-oleic sun¯ower oil may produce changes in the composition of VLDL triacylglycerols from hypertensive patients. It could be relevant for the uptake and metabolism of triacylglycerol-derived metabolites by extrahepatic tissues. Design: Patients were assigned to the diets in a random-order sequence. Subjects: The participants were 24 hypertensive patients recruited from a religious community. Interventions: The study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Although VLDL are triacylglycerol-rich lipoproteins with relevance in the development of atherosclerosis, the study of their triacylglycerol composition has been usually faced by analysing their fatty acid or total triacylglycerol content. Only exceptionally their triacylglycerol molecular species composition has been determined [9,10,11,19,20]. In the present study we report the achievement of the simultaneous determination of molecular species of triacylglycerols, but also of diacylglycerols and monoacylglycerols, which are products of the catabolism of VLDL triacylglycerols by LPL.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although VLDL are triacylglycerol-rich lipoproteins with relevance in the development of atherosclerosis, the study of their triacylglycerol composition has been usually faced by analysing their fatty acid or total triacylglycerol content. Only exceptionally their triacylglycerol molecular species composition has been determined [9,10,11,19,20]. In the present study we report the achievement of the simultaneous determination of molecular species of triacylglycerols, but also of diacylglycerols and monoacylglycerols, which are products of the catabolism of VLDL triacylglycerols by LPL.…”
Section: Discussionmentioning
confidence: 67%
“…In 1993, we presented for the first time the molecular species composition of VLDL underivatised triacylglycerol from human origin, analysed by gas-liquid chromatography (GLC) [9]. This method was then employed for the analysis of VLDL triacylglycerols from healthy and hypertensive subjects receiving diets rich in olive oil or high-oleic sunflower oil [10,11]. However, the analysis of triacylglycerols by GLC with flame-ionization detector (FID) presented deficiencies in the detection of the most unsaturated triacylglycerols [12].…”
Section: Introductionmentioning
confidence: 99%
“…The oils employed in the present study were selected to present differences in this lipid class: whereas VOO1 contained a greater amount of triolein, VOO2 was significantly enriched in species containing linoleic acid (Table 2). We have previously demonstrated that linoleoyl-species of triacylglycerols from HOSO were incorporated to a greater extent into chylomicrons and VLDL compared with VOO (Ruiz-Gutierrez et al 1999;Abia et al 1999Abia et al , 2001).…”
Section: Discussionmentioning
confidence: 98%
“…The main VLDL TAG structures of people on a high oleic acid diet were dioleoylpalmitoylglycerol and linoleoyloleoylpalmitoylglycerol (in Ref. 39, co-eluted with dioleoylpalmitoleoylglycerol), both comprising more than or nearly 20% of all TAG (39,40). Of the four M.W.…”
Section: Discussionmentioning
confidence: 98%